Superselective Transcatheter Arterial Embolization in the Treatment of Angiodysplasia - Leite, Túlio Fabiano de Oliveira (Clin Med Insights Case Rep, 2019)
Acute nonvariceal upper gastrointestinal hemorrhage is a frequent condition associated with significant morbidity and mortality. Angiodysplasia is a common cause of bleeding in the gastrointestinal tract in the elderly. This case report discusses about a 75-year-old woman clinically stable with melena for 2 years due to arteriovenous fistula of upper mesenteric artery branches without adequate clinical and therapeutic treatment. The goal of this article is to report the safety and efficacy of superselective transcatheter arterial embolization with coils in treating lower gastrointestinal bleeding caused by angiodysplasia that was unresponsive to internal medicine treatment and enteroscopy management.